2007
DOI: 10.1099/ijs.0.64205-0
|View full text |Cite
|
Sign up to set email alerts
|

dnaJ gene sequence-based assay for species identification and phylogenetic grouping in the genus Staphylococcus

Abstract: In the last few years, many attempts have been made to use conserved gene sequences for identification and for phylogenetic studies of Staphylococcus species. In an effort to identify a more reliable approach, a dnaJ gene sequence-based database was created. In this study, an approximately 883 bp portion of the dnaJ gene sequence from 45 staphylococcal type strains was compared with 16S rRNA and other conserved gene (hsp60, sodA and rpoB) sequences available in public databases. Nucleotide sequence comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 28 publications
4
95
1
Order By: Relevance
“…In addition, the partial sodA gene sequence failed to differentiate between the two subspecies of S. capitis, S. carnosus, S. saprophyticus and S. succinus and also the three subspecies of S. sciuri as the similarity among the subspecies was 100%. This finding is consistent with other conserved genes used for staphylococcal identification including dnaJ (Shah et al, 2007), hsp60 (Kwok and Chow, 2003) and 16S rRNA (Ghebremedhin et al, 2008;Kwok and Chow, 2003) where majority of complete discrimination at subspecies level was unsuccessful due to of high similarities among the subspecies.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the partial sodA gene sequence failed to differentiate between the two subspecies of S. capitis, S. carnosus, S. saprophyticus and S. succinus and also the three subspecies of S. sciuri as the similarity among the subspecies was 100%. This finding is consistent with other conserved genes used for staphylococcal identification including dnaJ (Shah et al, 2007), hsp60 (Kwok and Chow, 2003) and 16S rRNA (Ghebremedhin et al, 2008;Kwok and Chow, 2003) where majority of complete discrimination at subspecies level was unsuccessful due to of high similarities among the subspecies.…”
Section: Resultssupporting
confidence: 89%
“…In general, the results suggest that apart from the subspecies level, the sodA internal sequence is able to show more species discrimination as compared to the sequence of other conserved genes such as the 16S rRNA with mean similarity of 90% (Shah et al, 2007), rpoB with mean similarity of 86% (Drancourt and Raoult, 2002;Mellmann et al, 2006) and hsp60 with mean similarity of 82% (Kwok et al, 1999). Following general convention, a 95% identity threshold was adopted as the limit for a positive identification and unambiguous assignment to a particular species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates with scores ≥2.0 were identified to the species level according to manufacturer's guidelines. Each time an isolate displayed a score below 2.0, it was further identified by sequencing of the 16S rRNA gene using universal primers (Kuhnert et al, 1996) as well as by sequencing of the rpoB or dnaJ genes (Drancourt and Raoult, 2002;Shah et al, 2007). Its spectral profile was introduced into the MALDI-TOF MS database thereafter.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The taxonomy of the genus Bacteroides has undergone significant changes in the last two decades (Dewhirst et al, 1990;Moore & Moore, 1994;Rautio et al, 2003;Sakamoto et al, 2002Sakamoto et al, , 2007Sakamoto & Benno, 2006;Shah & Collins, 1988. It has also been reported that 16S rRNA gene sequencing is useful for the identification of isolates of clinically significant species of the genus Bacteroides (Song et al, 2005).To date, a multilocus sequence typing (MLST) approach has been widely used to infer the phylogeny of organisms (Alexandre et al, 2008; Itoh et al, 2006;Shah et al, 2007;Yamamoto & Harayama, 1995). However, only limited information has been accumulated for species of the genus Bacteroides.…”
mentioning
confidence: 99%